Kuasa, Tubuh, dan Tanda dalam Meme Politik Pasangan Fiktif Nurhadi-Aldo pada Pilpres 2019 - Yuristia Wira Cholifah; Aditya Eko Adrianto (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2019)
This article discusses how power, body and leftism exist in political memes of NurhadiAldo. Indonesia recently has witnessed the emergence of a pair of fictitious presidential candidates, Nurhadi-Aldo. The pair emerged amid mounting political tension ahead of the Indonesian presidential election for the 2019-2024 period. This fictional couple suddenly became viral with various uploaded memes that seem to be vulgar - related to the body, but some uploads voiced criticism against power. Nurhadi-Aldo, then abbreviated as ‘Dildo’, symbolizes itself as a fake phallus, a fictitious power. This study uses a qualitative method with Peirce’s semiotic approach. Based on the semiotic analysis of Nurhadi-Aldo (NA) meme samples related to power and body, it can be concluded as follows: (1) Political memes can be a medium of aspiration for all parties that are humorous, but effective and viral; (2) The NA Meme comes from two shitposting icons, so NA memes will always cover body, irony, and absurdity; (3) Shitposting which tends to be vulgar and aggressive allows NA meme to bring sensitive topics, especially leftism and body; (4) The appearance of the inverted NA profile photo and the abbreviation attached to them – dildo has an important role in building a symbol of fictitious power.